Recruiting and Preparing Undergraduate Students for a Collegiate Debate: An HBCU Case Study - Wordlaw, LaShawn; Harrell, Kevin J.; Romocki, LaHoma Smith (Frontiers in Education, 2021)
The benefits of debate as an effective pedagogical tool in higher education are well-published. It fosters students’ development of critical thinking, collaboration, creativity, and communication skills. This paper describes a conceptual model of debate categories: in-class debate, co-curricular debate, and tournament debate. It proposes six levels of debate for faculty to employ to create engaged active learning experiences. It is a case study written from the perspective of faculty who served as debate coaches over a four-year period. It shares lessons learned and best practices for recruiting and preparing undergraduate students for a co-curricular debate competition, a subject that is missing in the literature.